MAGNETIC FIELD EFFECT ON THE CHANGE IN REDOX POTENTIAL OF AQUEOUS SOLUTIONS - Savchenko, V.; Sinyavsky А.; Nazarenko, I. (Енергетика і автоматика, 2016)
The results of studies of changes in redox potential of aqueous solutions under the influence of a magnetic field are shown. The dependence of redox potential of aqueous solutions of salts from the regime of processing parameters in a magnetic field are established. The optimal processing parameters are defined.